2021
DOI: 10.1021/acscatal.1c02790
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Imperative Role of Metal–Olefin Interactions in Catalytic C–O Reductive Elimination from Nickel(II)

Abstract: We present a series of experimental and computational mechanistic investigations of an unusually facile example of Ni-catalyzed C–O bond formation. Our method, originally reported in 2016, involves the formation of cyclic enol ethers from vinyl iodides bearing pendant alcohol groups. Our findings suggest that the observed reactivity arises from the coordination of the olefin in the vinyl iodide starting material and the enol ether product with Ni(0) intermediates. Density functional theory calculations reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…With these modifications, we were able to isolate and characterize [Ni I (COD)­Br] 2 ( 5 ), a golden yellow solid that is stable at −35 °C under inert atmosphere (Figure ). , 5 is a rare example of a Ni I –olefin complex and a tractable precursor to a variety of Ni I –Br complexes (vide infra).…”
Section: Resultsmentioning
confidence: 99%
“…With these modifications, we were able to isolate and characterize [Ni I (COD)­Br] 2 ( 5 ), a golden yellow solid that is stable at −35 °C under inert atmosphere (Figure ). , 5 is a rare example of a Ni I –olefin complex and a tractable precursor to a variety of Ni I –Br complexes (vide infra).…”
Section: Resultsmentioning
confidence: 99%
“…With these modifications, we were able to isolate and characterize [Ni I (COD)Br]2 (5), a golden yellow solid that is stable at -35 °C under inert atmosphere (Figure 4). 46,47 5 is a rare example of a Ni I -olefin complex and a tractable precursor to a variety of Ni I -Br complexes (vide infra). to generate LnNi I complexes with bulky monophosphines.…”
Section: Resultsmentioning
confidence: 99%
“…Transition metal-catalyzed selective C–H functionalization of hydrocarbons is one of the major challenges of organometallic chemistry. This transformation involves a number of fundamental steps such as oxidative addition (OA), β-hydride elimination, migratory insertion, and reductive elimination (RE). ,, RE reactions are critical for the final product-forming step. To reduce deleterious side reactions and enhance overall catalyst efficiency, the metal must undergo the appropriate series of fundamental reactions with great selectivity . Understanding the parameters that influence the selectivity of these reactions is key to designing and improving novel transition metal-catalyzed transformations. High-valency octahedral metal complexes have more donor ligands at the metal center than their more common square planar counterparts, which may indicate greater competitiveness in the formation of C–C or C–X (X = heteroatom such as O, N, and S) bonds and thus require greater control over the reaction selectivity. , For instance, as different research groups have reported, competitive carbon–carbon and/or carbon–heteroatom bond RE can be seen at Pt­(IV) and Pd­(IV) centers in a single complex. , Notably, high-valency d 6 metal systems typically prefer the C–C over the C–X coupling reaction, though exceptions to this trend have been noted. , On the other hand, the formation of new C–C or C–X (X = heteroatom) bonds through RE from a M­(IV) center (group 10) constitutes the product-forming step in various catalytic oxidative transformations that have garnered considerable attention over the past 2 decades. , Despite some noteworthy advancements in this field, mechanistic studies in selective C–X vs C–C bond RE reactivity have not been extensively investigated. ,, Furthermore, the chemoselectivity of C–X bond RE is poorly known in systems where different competing coupling reactions may occur . As a result of their kinetic inertness, Pt­(IV) compounds can be considered excellent models for studying these coupling processes. ,,…”
Section: Introductionmentioning
confidence: 99%